A utilização de material concreto para o ensino inclusivo da matemática na educação básica: Um estudo de campo no estado do Amapá - CARDOSO, Alerrandresson Araújo (Instituto Federal do Amapá, 2021)
This report brings a case study carried out in the State of Amapá based on the possibility of more inclusive aspects within the reality of the teaching of mathematics, bringing an activity with the use of two games adapted to the Brazilian Sign Language - LIBRAS. Thus, the general objective of this report was to increase mathematical curiosity in students, providing inclusion in the classroom and outside it. Thus, we seek to instigate the student's learning and improve his logical reasoning. To obtain the results, it was based on the following specific objectives: verify student learning through the use of games; validate the possibility of satisfactory results with the use of concrete materials in the teaching of mathematics; strengthen the inclusion process within the teaching of mathematics, bringing the use of LIBRAS to the teaching context. We opted to use the field study as a methodology, as we sought to deepen the knowledge about the use of games for Elementary School students in an applied school in the State of Amapá, in the city of Macapá, investigating the data from the qualitative method, the practical question highlighted the importance of working with the teaching of mathematics interdisciplinarly with activities aimed at Libras for this audience, since this discipline is considered complicated for students. The work was carried out at the Maria Neusa do Carmo School in September 2019, with students from the 8th year of Elementary School II, where the activity was developed in a playful way, with questionnaires and surveys aimed at LIBRAS and the teaching of mathematics in daily life. Therefore, in the results it was possible to conclude that all 10 students who participated, liked the use of mathematics teaching with LIBRAS. In this way, students were able to learn the numbers presented in LIBRAS, and thus, strengthening the concepts of basic mathematics in their daily lives.